A Pilot Study Examining the Relationship Between Patients' Complaints and Scores on the Hirschfeld Mood Disorder Questionnaire - Gorski, Eugene (Physicians Postgraduate Press, Inc., 2003)
Introduction: The incidence of bipolar disorder in the general population has been estimated at approximately 5%. The purpose of this study was to establish a relationship between patients' complaints on arrival to a primary care clinic and their subsequent scores on the Hirschfeld Mood Disorder Questionnaire (MDQ). Method: After reviewing data obtained from 178 consecutive patients, 171 were found adequate for study inclusion. The inclusion criteria for this study were presentation to a family practice office for care regardless of complaint and age of 18 years or older. Study participants were asked to complete a historical/demographic questionnaire, which gathered data on primary and secondary complaints and medication history, and the MDQ. Results: Thirty patients (17.5%) tested positive on the MDQ for bipolar symptoms; all were aged 65 years or under. Of those who tested positive, 20% (N = 6) presented with a primary complaint of anxiety or depression. Somatic primary complaints of pain and headache carried a high likelihood of secondary complaints of anxiety or depression. Conclusion: Patients with complicated or multiple somatic complaints in primary care may also have concomitant undiagnosed bipolar disorder. Clinicians should use a high index of suspicion for the diagnosis of bipolar disorder when treating patients with these assessment characteristics. Further research is necessary to determine if these trends are applicable in a larger population.